Humphrey visual field made easy for residents - Tarannum Mansoori (Indian Journal of Ophthalmology, 2024)
Background: Visual field testing is an indispensable part of the assessment of glaucoma. Of paramount importance to both the practitioner and the perimetrist is the guidance on how to conduct the test to get the best results and also the interpretation of test results. Purpose: To simplify the basics of understanding single-field analysis of visual field tests by using the Humphrey perimeter. Synopsis: The general principle and a brief overview of how the Humphrey visual field is conducted and the approach to interpreting the results of single field analysis in an easy-to-understand manner are presented. Highlights: This educational video is an attempt to simplify the interpretation of Humphrey visual field single-field analysis with illustrations and video clips that would be useful to practicing ophthalmologists and optometrists and in training programs. Video link: https://youtu.be/x8iZLDR4XdY.